Evaluation of the implementation of the 2013 curriculum reviewed from the aspect of the learning process and assessment of learning outcomes (case study: SMA / SMK / MA Pringsewu regency) - Trisnawati Trisnawati; Leni Anggraeni; Winia Waziana; Dian Puspita (Jurnal Penelitian Ilmu Pendidikan, 2019)
This study aims to determine and evaluate the implementation of the 2013 curriculum specifically in aspects of the learning process and aspects of assessment of learning outcomes. This study is a qualitative descriptive study, with the population being SMA / SMK equivalent in Pringsewu Regency while the sample is 10 high school / SMK level schools in Pringsewu Regency selected from 9 different sub regency. In terms of the learning process aspect, achieving the highest percentage is the teacher's understanding of the subject matter in student textbooks, while the lowest percentage is the suitability of learning procedures with a scientific approach. In terms of the assessment of learning outcomes, the highest percentage achievement is the teacher's understanding of the concepts and applications of midterm tests, while the lowest percentage is the teacher's understanding of portfolio-based assessment concepts and applications. The results of the overall analysis show that, in terms of the learning process aspects and assessment of learning outcomes, the implementation of K-13 at the SMA/SMK/MA level in Pringsewu Regency was in a good category although there were still a few things that needed to be improved.Evaluasi implementasi kurikulum 2013  ditinjau dari aspek proses pembelajaran dan penilaian hasil belajar (studi kasus: SMA/SMK/MA Kabupaten PringsewuPenelitian ini bertujuan untuk mengetahui dan mengevaluasi implementasi kurikulum 2013 khususnya dalam aspek proses pembelajaran dan aspek penilaian hasil belajar. Penelitian ini merupakan penelitian deskriptif kualitatif, dengan populasinya adalah SMA/SMK sederajat di kabupaten pringsewu lampung sedangkan sampelnya adalah 10 SMA/SMK sederajat di kabupaten Pringsewu Lampung yang dipilih dari 9 kecamatan yang berbeda. Ditinjau dari aspek proses pembelajaran, pencapaian persentase tertinggi adalah pemahaman guru tentang materi pelajaran yang ada di buku pelajaran siswa, sedangkan persentase terendah adalah kesesuaian prosedur pembelajaran dengan pendekatan saintifik. Ditinjau dari aspek penilaian hasil belajar, pencapaian persentase tertinggi adalah pemahaman guru tentang konsep dan aplikasi ulangan tengah semester, sedangkan persentase terendah adalah pemahaman guru tentang konsep dan aplikasi penilaian berbasis portofolio. Hasil analisis secara menyeluruh menunjukkan bahwa ditinjau dari aspek proses pembelajaran dan penilaian hasil belajar, implementasi K-13 di tingkat SMA/SMK/MA di kabupaten Pringsewu berada pada kategori baik meskipun masih ada beberapa hal yang perlu diperbaiki.